PENGARUH KELELAHAN EMOSIONAL, KOMPETENSI DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA PENYULUH KELUARGA BERENCANA (Studi Pada Kantor Perwakilan Badan Kependudukan dan Keluarga Berencana Nasional Provinsi Sulawesi Tenggara) - Muslimin Muslimin (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
The purpose of this study was to examine and examine: 1) the effect of emotional exhaustion, competence and quality of work life simultaneously on the performance of the Family Planning Extension Officer at the Representative Office of the National Population and Family Planning Agency of Southeast Sulawesi Province. 2) the effect of emotional exhaustion partially affects the performance of the Family Planning Counselor at the Representative Office of the National Population and Family Planning Agency of Southeast Sulawesi Province. 3) the influence of competence partially affects the performance of the Family Planning Extension Officer at the Representative Office of the National Population and Family Planning Agency of Southeast Sulawesi Province. 4) the influence of the quality of work life partially affects the performance of the Family Planning Extension Officer at the Representative Office of the National Population and Family Planning Agency of Southeast Sulawesi Province.This research design uses a quantitative approach, with the type of explanatory research. The sampling technique in this study is proportional random sampling, which is a method of taking samples from members of the population using a random method without regard to the strata in the population as many as 166 respondents. The data used are primary and secondary data. The data analysis method of this research is descriptive analysis and multiple linear regression analysis. The results showed that: 1) Emotional exhaustion, competence, and quality of work life simultaneously had a significant effect on improving the performance of the extension worker at the Representative Office of the National Population and Family Planning Agency of Southeast Sulawesi Province. 2) Emotional exhaustion has a positive and significant effect on the performance of the extension worker at the Representative Office of the National Population and Family Planning Agency of Southeast Sulawesi Province. 3) competence has a positive and significant effect on the performance of the extension worker at the Representative Office of the National Population and Family Planning Agency of Southeast Sulawesi Province. 4) The quality of work life has a positive and significant effect on the performance of the extension worker at the Representative Office of the National Population and Family Planning Agency of Southeast Sulawesi Province.